On the adsorption of n-butane on alkyl imidazolium ionic liquids with different anions using a new molecular beam setup - Winter, Leonhard; Bhuin, Radha Gobinda; Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Journal of Chemical Physics, 2020)
The adsorption of reactants is an elementary step in the interaction of molecules with liquid or solid surfaces. We recently reported on the trapping of n-butane on the frozen surfaces of ionic liquids (ILs), namely, 1-Alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ILs ([CnC1Im][Tf2N]; n = 1, 2, 3, and 8). To study the influence of the anion, we now present results concerning the trapping of n-butane on 1-Alkyl-3-methylimidazolium hexafluorophosphate ILs ([CnC1Im][PF6]; n = 2, 4, and 8), that is, ILs with a smaller anion. The adsorption energies close to zero coverage are determined from the temperature dependence of the initial trapping probability using a novel approach. For both groups of ILs, the binding energy is dominated by the interaction of n-butane with the alkyl chain of the cation, whereas the ionic headgroups contribute only weakly. Comparing ILs with different alkyl chains at the IL cation, we find that the adsorption strength of n-butane increases with increasing length of the alkyl chain. In addition, detailed information on the new setup and the data analysis is provided.
CRIS-Team Scopus Importer:2020-12-25